Euro area reform preferences of Central and Eastern European economic experts - Sebastian Blesse; Annika Havlik; Friedrich Heinemann (Empirica, 2020)
This study explores the positions of economic experts from Central and Eastern European (CEE) Member States in the euro reform debate. Given the dominant voices from French and German politicians and academics in the European discourse, there is an obvious neglect for the positions of CEE countries. Our study tries to fill this gap with a large survey among economic expert communities in all CEE countries conducted in spring 2019. We compare euro reform preferences to benchmarks of surveyed experts in France, Germany, and Italy. We discuss implications for the ongoing euro area reform with a particular focus on several non-euro members' growing reluctance to introduce the common currency. We argue that only a balanced reform package that combines solidarity with debt self-responsibility could foster the euro's appeal in the CEE region.
Keywords: A11; E63; H63; 330; Euro reform debate; European Integration; Central and Eastern Europe; Expert survey